ARSITEKTUR BUDAYA TUGU: SEBUAH KONSEP PENGEMBANGAN KAWASAN SEJARAH PERKAMPUNGAN PORTUGIS DI JAKARTA UTARA - Natasya, Shela; Hadiwono, Alvin (Jurusan Arsitektur dan Perencanaan, 2024)
Kampung Tugu is one of the oldest villages in Jakarta, having been established in 1678. Kampung Tugu is known as a Christian-Portuguese village which is a cultural heritage area. The cultural heritage in Tugu Village is in the form of a building known as the Tugu Church. Currently, Kampung Tugu is undergoing changes, with most of the surrounding land now being used for container parking and industrial activities. As a result, Kampung Tugu area looks less attractive, and not many people know about this tourist area and create a placeless impression. The purpose of this research is to develop the historical tourism area in an effort to revive the memory of Tugu Culture consisting of Mande-Mande and Rabo-Rabo traditions as well as Keroncong music, which are the characteristics of the area of Kampung Tugu which must be preserved. Developing the tourist area and insight of Kampung Tugu by adding cultural attractions in the form of a cultural space that focuses on preserving keroncong music and introducing typical culinary delights from Kampung Tugu. It is hoped that this cultural space can become the new face of Kampung Tugu to maintain the continuity of its existence, revive the character of the area and open new spaces in the hope that it can accommodate the surrounding area and become an attraction for the outside community. The design uses an adaptive and contextual design approach to the surroundings that responds to modern conditions. Keywords: cultural heritage; historical tourism; kampung tugu; tugu culture Abstrak Kampung Tugu termasuk sebagai kampung tertua di Jakarta, yang sudah ditetapkan sejak tahun 1678. Kampung Tugu dikenal sebagai kampung Kristen – Portugis yang termasuk kawasan cagar budaya. Cagar budaya yang ada di Kampung Tugu berupa sebuah bangunan yang dikenal sebagai Gereja Tugu. Saat ini Kampung Tugu mengalami perubahan, dengan sebagian besar lahan di sekitarnya kini digunakan untuk parkir kontainer dan kegiatan industri. Adanya perubahan membuat Kawasan Kampung Tugu menjadi terlihat kurang menarik, tergolong tidak banyak yang mengetahui mengenai kawasan sejarah ini dan terciptanya kesan placeless. Penelitian ini bertujuan untuk mengembangkan kawasan menjadi wisata sejarah sebagai upaya membangkitkan kembali memori dari budaya tugu yang terdiri dari, Tradisi Mande-Mande dan Rabo-Rabo serta musik Keroncong, yang menjadi karakter kawasan dari Kampung Tugu yang harus dilestarikan. Mengembangkan area wisata dan wawasan Kampung Tugu dengan penambahan atraksi budaya dalam bentuk ruang kebudayaan yang berfokus pada pelestarian musik keroncong dan mengenalkan kuliner khas dari Kampung Tugu. Ruang kebudayaan ini diharapkan dapat menjadi wajah baru Kampung Tugu untuk menjaga keberlanjutan dari eksistensi untuk menghidupkan karakter kawasan dan membuka ruang baru dengan harapan dapat mewadahi sekitar dan menjadi daya tarik bagi masyarakat luar. Perancangan menggunakan metode pendekatan desain yang adaptif dan kontekstual terhadap sekitar yang merespon kondisi modern.